2010
DOI: 10.1016/j.jvs.2009.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase affects both early and late collateral arterial adaptation and blood flow recovery after induction of hind limb ischemia in mice

Abstract: Objective The goals of this study were to determine if endothelial nitric oxide synthase (eNOS) affects both early and late collateral arterial adaptation and blood flow recovery after severe limb ischemia, and to determine if eNOS-derived NO was necessary for recruitment of CXCR4+ VEGFR1+ hemangiocytes to the site of ischemia. Methods and Results Two studies were carried out. In the first study, hindlimb ischemia was induced by unilateral femoral artery excision in 3 groups: C57Bl6 (wild type), eNOS-/-, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Both eNOS and NO production are increased during arteriogenesis, and blocking NO production with L-NAME or eNOS knockout inhibits collateral growth in several models of arteriogenesis (27,33,36,60). We verified that the high-FSS A: high, but not normal, FSS significantly increased nitrate/nitrite levels immediately after shear exposure compared with static control (n ϭ 5).…”
Section: Effect Of Fss On Plgf Mrna Expression In Hcaec (Ec) and Hcsupporting
confidence: 51%
“…Both eNOS and NO production are increased during arteriogenesis, and blocking NO production with L-NAME or eNOS knockout inhibits collateral growth in several models of arteriogenesis (27,33,36,60). We verified that the high-FSS A: high, but not normal, FSS significantly increased nitrate/nitrite levels immediately after shear exposure compared with static control (n ϭ 5).…”
Section: Effect Of Fss On Plgf Mrna Expression In Hcaec (Ec) and Hcsupporting
confidence: 51%
“…Rats provided with two (BH4 + L-arginine) or three (BH4 + L-arginine + vitamin C) supplements showed significantly greater recovery of foot perfusion than rats fed normal chow or rats given a single dietary supplement. This difference was evident at the later phase of recovery, on d 21, 28 or 42 after induction of ischemia, which was also the time of maximal collateral artery wall remodeling (20). A similar pattern was noted for collateral artery angioscores determined on d 42 after induction of ischemia.…”
Section: Effects Of Bh4 L-arginine and Vitamin C On Hindlimb Perfusionsupporting
confidence: 67%
“…Previous study found that activation of eNOS is impaired in diabetic bone marrow, resulting in the deficiency of endothelial progenitor cells mobilization [33]. In addition, observations indicated that eNOS-derived NO is requisite for acute adaptation to severe ischemia to prevent tissue necrosis and for sustained arteriogenesis [34]. Leung et al [15] have shown that Rg1 can increase phosphorylation and the activities of PI3K, Akt, and eNOS, leading to increased NO production in HUVECs.…”
Section: Discussionmentioning
confidence: 97%